The effect of fatigue on choice of technique and physiological response in cross-country skiing - Ettema, G.; Øksnes, M.; Kveli, E.; Sandbakk, O. (NVC Conference 2017, 5.-6. October 2017, Are, Sweden, 2017)
Background and Aim:Cross-country skiing in hilly terrain elicits use of different sub-techniques. Both the choice of technique as well as fatigue in competition may affect the physiological response. Therefore, the effect of fatigue under variable terrain conditions with free choice of technique is multidimensional given the complex interaction of terrain (incline), skiing speed, technique, and physiological response. Here, we studied how fatigue influenced technique choice and physiological responses during variable incline and speed conditions, but at constant external work rate. Methods: Eight well-trained athletes performed a 21-minute treadmill roller skiing protocol at 200 Watts, before (PRE) and after (POST) exhaustive skiing (by an incremental protocol). During the PRE and POST protocol, incline was both increased and decreased by 1% each minute (3% - 11% - 3%), while speed was altered accordingly to maintain the constant workload. The choice of technique, VO2, RER, and heart rate were recorded continuously. ANOVA for repeated measures was used for statistical analysis. Results: Technique choice and cycle rate were hardly affected by fatigue. After fatigue, an enhanced VO2 was obtained during the first 6 minutes, with heart rate remaining elevated (by ~10 bpm) during the entire protocol after fatigue. RER was reduced during the entire POST protocol. Conclusion: The fatigue induced a lasting enhanced physiological response, but metabolic cost returned to fresh state levels. In combination with unaltered choice of technique and cycle rate, this indicates that technical execution is unaffected.